Revisiting the Coreceptor Function of Complement Receptor Type 2 (CR2, CD21); Coengagement With the B-Cell Receptor Inhibits the Activation, Proliferation, and Antibody Production of Human B Cells - Kovács, Kristóf G.; Mácsik-Valent, Bernadett; Matkó, János; Bajtay, Zsuzsa; Erdei, Anna (Frontiers in Immunology, 2021)
The positive coreceptor function of CR2 (CD21) on B cells is generally accepted, although its role in the enhancement of antibody production had only been proven in mice. Due to the importance of this phenomenon, we reinvestigated the functional consequences of coclustering CD21 and the B cell receptor (BCR) on primary human cells. We found that at non-stimulatory concentrations of anti-IgG/A/M, coclustering the BCR and CR2 enhanced the Ca2+ response, while activation marker expression, cytokine production, proliferation and antibody production were all inhibited upon the coengagement of CR2 and BCR on human B cells. Thus the “textbook dogma” claiming that C3d acts as an adjuvant to enhance humoral immunity is relevant only to mice, not to men.